2020
DOI: 10.2147/ijn.s236277
|View full text |Cite
|
Sign up to set email alerts
|

<p>Novel Approach for Transdermal Delivery of Rifampicin to Induce Synergistic Antimycobacterial Effects Against Cutaneous and Systemic Tuberculosis Using a Cationic Nanoemulsion Gel</p>

Abstract: This study demonstrated improved transdermal delivery of rifampicin-loaded cationic nanoemulsion gel to treat systemic and cutaneous tuberculosis using capmul, labrasol, and acconon, which exert anti-Mycobacterium activities. This approach enhanced drug permeation across the skin, increased therapeutic efficacy, and reduced dose-related side effects. Methods: Design Expert ® was used to optimize formulations (S mix ratio and capmul as independent factors), which were prepared using a slow spontaneous titration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…Rifampicin was assayed using a previously established method [ 25 ]. The drug content was estimated using a RP-C 18 column (150 × 4.6 mm, 5 μm, Purospher Star, Merck, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rifampicin was assayed using a previously established method [ 25 ]. The drug content was estimated using a RP-C 18 column (150 × 4.6 mm, 5 μm, Purospher Star, Merck, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…RIF is poorly soluble in water (~1–2 mg/mL) at 25 °C, whereas it is soluble in CMC8, DMSOT, and isopropyl alcohol [ 24 , 25 ]. Therefore, we added DMSOT (5% v / v ) in an aqueous medium for stock solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The titration phenomenon presented started turbid to clear, and ended clear to turbid. 25 However, a few research papers showed a point, not a region in the procedure of their pseudo-ternary phase diagrams construction, 26,[39][40][41][42] this question needs to be deliberated. Figure 3 exhibited the picture taken under optical microscope, DMNs dyed with methylene blue and the droplet was colored blue on the outside.…”
Section: The Outcome Of Oil Phase Screeningmentioning
confidence: 99%
“…So it is theoretically speculated that the DMNs should be relatively safe and non-toxic. But the body processes, absorption sites, 42,45 as well as long-term toxicity of DMNs, have not been performed. Third, during the gastroscopy to observe the effect of the drug, administered via the tube injection method 13 (the insertion of a plastic tube through a gastroscopy biopsy hole) is a reliable scheme to evaluate the effect of drug, which can be used to show the contrast before and after administration.…”
Section: Utilizing Effects Of Egementioning
confidence: 99%